2011
DOI: 10.1002/hyp.8129
|View full text |Cite
|
Sign up to set email alerts
|

On the usefulness of remote sensing input data for spatially distributed hydrological modelling: case of the Tarim River basin in China

Abstract: Abstract:The ecological situation of the Tarim River basin in China seriously declined since the early 1950s, mainly due to a strong increase in water abstraction for irrigation purposes. To restore the ecological system and support sustainable development of the Tarim River basin region in China, more hydrological studies are demanded to properly understand the processes of the watershed and efficiently manage the water resources. Such studies are, however, complicated due to the limited data availability, es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 41 publications
1
29
0
Order By: Relevance
“…But they agree with other researchers that incorporating additional site-specific information in a distributed hydrological model increases its robustness (Stisen et al, 2011). Especially remote sensing data are valued as a useful complement to station based time series (Finger et al, 2011;Liu et al, 2012).…”
Section: Improving Spatial Representativeness Of Distributed Modelssupporting
confidence: 83%
“…But they agree with other researchers that incorporating additional site-specific information in a distributed hydrological model increases its robustness (Stisen et al, 2011). Especially remote sensing data are valued as a useful complement to station based time series (Finger et al, 2011;Liu et al, 2012).…”
Section: Improving Spatial Representativeness Of Distributed Modelssupporting
confidence: 83%
“…The microwave satellite precipitation have also drawn increasing attention in hydrologic modelling. For example, the precipitation estimates from Chinese meteorological satellite Fengyun-2C were tested in the Tarim River Basin for streamflow simulation with the distributed MIKE SHE model, and it has been found that microwave satellite provided relatively high spatial resolution precipitation in sparsely gauged areas which exhibited positive impact on flow simulation especially during summer time [78].…”
Section: Implementation Of Satellite Precipitationmentioning
confidence: 99%
“…Daniel (2011) gives a good comparison of different frequently used models but the number of different models is simply too large to be covered entirely. The integration of raster data sets has been implemented in different models such as the MIKE SHE (Cooper et al, 2006;Liu et al, 2012) or CREST (Khan et al, 2011) models, and several more examples of raster data input are available (Merritt et al, 2006;Stahl et al, 2008;Wood et al, 2004). While each of these models has specific qualities, none of them globally outperforms the others.…”
Section: Hydrological Modellingmentioning
confidence: 99%
“…This is due to the high computational expense that is needed to create such data sets. The abundance and increasing accuracy in GCMs, RCMs, and remote sensing data has led to their greater use in hydrological modelling (Khan et al, 2011;Awange et al, 2011;Liu et al, 2012;Bookhagen and Burbank, 2010) and glacier evolution studies (Gardelle et al, 2012(Gardelle et al, , 2013Lutz et al, 2014;Sorg et al, 2012). In cold, arid, mountainous regions, GCMs are often favoured over remote sensing data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation